Diagnosis dan Tatalaksana Fraktur Klavikula: Tinjauan Pustaka - Waton, Hisbul; Ismunandar, Helmi (CV. Jasa Sukses Abadi, 2026)
Clavicle fracture is one of the most common fractures of the upper extremity, resulting from either direct or indirect trauma to the shoulder with the arm positioned alongside the body. This injury is more frequently observed in young adult males, commonly due to traffic accidents, while in the elderly population it is often caused by falls. Clavicle fractures typically present with severe pain, swelling, shoulder deformity, and may be accompanied by neurovascular impairment, necessitating comprehensive clinical evaluation. Physical examination includes inspection, palpation, assessment of shoulder range of motion, and neurovascular evaluation such as the Allen test to assess collateral blood flow. Diagnostic confirmation is supported by imaging modalities including standard anteroposterior radiographs, 30° cephalad tilt view, apical oblique view, and computed tomography scan for complex fracture patterns and preoperative planning. The management of clavicle fractures aims to reduce pain, prevent disability, restore upper limb function, and consider cosmetic outcomes. Treatment options include nonoperative management using an arm sling or figure-of-eight brace for stable fractures, as well as operative management for unstable fractures or those associated with neurovascular complications. Post-treatment rehabilitation plays a crucial role in gradually restoring shoulder range of motion and functional recovery.